Inkjet Printing of an Electron Injection Layer: New Role of Cesium Carbonate Interlayer in Polymer OLEDs - C, Amruth (Polymers (Basel), 2020)
Among solution-processable techniques, inkjet printing is a potential method for manufacturing low-cost and high-resolution polymer organic light-emitting diodes (PLEDs) for displays/solid-state lighting applications. Herein, we demonstrate use of the inkjet printed cesium carbonate (Cs(2)CO(3)) film as an electron injection interlayer. We have elaborated the Cs(2)CO(3) ink using an alcohol-based solvent for the industrial-grade printhead. The printed Cs(2)CO(3) layer morphology was investigated by means of an optical microscope and an atomic force microscope. The PLEDs based on emissive polymer (Super Yellow) with printed Cs(2)CO(3) interlayer show a remarkable current efficiency and luminance compared to the PLEDs made without the Cs(2)CO(3) layer. Such results suggest that the Cs(2)CO(3) is a promising material for the formulation of the electron injecting inkjet inks. The possibility of inkjet printing of an efficient electron injecting layer enables in situ patterning of PLEDs’ emission area. Such a simple and flexible technique can be applied for a wide range of applications such as signage, pictograms, advertising, smart packaging, etc.